Møller's Energy in the Kantowski-Sachs Space-Time - M. Abdel-Megied; Ragab M. Gad (Advances in High Energy Physics)
We have shown that the fourth component of Einstein's complex for the Kantowski-Sachs space-time is not identically zero. We have calculated the total energy of this space-time by using the energy-momentum definitions of Møller in the theory of general relativity and the tetrad theory of gravity.